DETERMINATION OF THE TEMPERATURE FIELD DURING LASER COAGULATION of CHORIORETINAL COMPLEX WITH OPTOACOUSTIC IN VITRO - A. V. Ardamakova; N. A. Fedoruk; A. P. Lytkin; A. V. Larichev; V. I. Siplivyy (Сибирский научный медицинский журнал)
The article describes a determination method of the laser radiation with specific parameters effect on the eye tissues based on optoacoustic probing. Low-power probing laser with 7-10 ns pulses generates acoustic waves at the aiming point. The waves propagate through the medium (saline in a cuvette) to acoustic receiver. The characteristics of the acoustic wave give basis for estimation of optical absorption coefficient - a parameter that determines temperature in the affected area after applying therapeutic laser. Calculation of the temperature pattern was performed using a three-dimensional thermal conductivity model that enabled determination of temperature distribution at any local point during coagulation and immediately after. To compare the results with pre-calculated temperature field values, direct temperature measurement was taken from the surface of the absorbing layer. The experiment was performed on six human chorioretinal tissue samples in vitro; the obtained optical absorption coefficient values did not exceed 120-300 cm-1 with maximum error margin of 20 %. The computational model was seen to be in good agreement with experimental thermocouple measurements.